The Effect of Non Perfoming Financing and Financing to Deposit Ratio On Return On Assets - Ahmad Iskandar Rahmansyah; Nasya Salsabila Balqis; Yekti Rahajeng; M. Syarif Hidayatullah Elmas; Siti Masluha (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
Credit and liquidity risk analysis is one of the way to view the health of a bank, especially the development of Islamic bank in Indonesia. Some of previous studies examined the effect of credit risk and liquidity on the profitability of Islamic banks, but the results were not consistent. Therefore, this study uses credit risk (Non Performing Financing) and liquidity risk (Financing to Deposit Ratio) as variables that affect the profitability (Return on Assets) of Islamic banks. The sample of this study is 4 Commercial Banks of Islamic Exchange that listed on the Indonesian stock exchange during the 2014-2018 period. The research data is the annual report of bank which is obtained from the Indonesian Stock Exchange website and the data is processed by using multiple regression models. The result of this study indicates that Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) have a negative effect on Return on Assets (ROA).